The sensitivity of the mode instability threshold to different types of intensity noise - Stihler, Christoph; Jauregui, Cesar; Kholaif, Sobhy E.; Limpert, Jens (Proceedings of SPIE - The International Society for Optical Engineering, 2020)
In this work we experimentally and theoretically investigate the impact of seed intensity-noise on the threshold of transverse mode instability (TMI) in Yb-doped, high-power fiber laser systems and compare it to the impact of pump intensity-noise. Former studies have shown that pump intensity-noise significantly decreases the TMI threshold due to the introduction of a phase shift between the modal interference pattern and the thermallyinduced refractive index grating in the fiber. However, it can be expected that fluctuations of the seed power will also induce such phase shifts due to a change of the extracted energy and the heat load in the fiber. Thus, it is important to investigate which one, i.e. the seed-or the pump intensity-noise, has a severer impact on the TMI threshold. Our experiments have shown that the TMI threshold of a fiber amplifier was decreased by increasing the seednoise amplitude. However, contrary to conventional belief, the impact of seed intensity-noise was much weaker than the one of pump intensity-noise. The measurements are in good agreement with our simulations and can be well explained with previous studies about the noise transfer function. The reason for the weaker impact of seed intensity-noise on the TMI threshold is the attenuation of its frequency components below 20 kHz in saturated fiber amplifiers, which includes the frequencies relevant for TMI. Thus, the main trigger for TMI in saturated fiber amplifiers can be considered to be pump intensity-noise. A suppression of this noise below 20 kHz represents a promising way to increase the TMI threshold of fiber laser systems.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Fiber laser; Modal interference pattern; Mode instability; Phase shift; Pump intensity-noise; Refractive index grating; Seed intensity-noise; Thermal effects in optical fibers